Estrutura e custo de capital: um estudo em empresas brasileiras de nanotecnologia - Milena de Cássia Rocha (2015)
This thesis sought to analyze how the capital structure of nanotechnology companies in Brazil is set, having as a starting point their assessing of capital cost, their adopted structure and some of their funding sources relevance. A case study was conducted where TBCs were inserted in the nanotechnology segment. The research was descriptive, quantitative and qualitative. At the quantitative approach, WACC simulation was held to Brazilian nanotechnology companies in distinct levels of debt, through Monte Carlo simulation technique. At the qualitative stage, semi-structured interviews were conducted with managers, seeking to confirm the data found in the quantitative phase and the understanding of the adopted capital structure and the way in which it is defined, as well as the relevance of some funding sources. Epistemological stance of functionalist and positivist character were adopted. Among the results, the analyzed companies have a capital structure consisting of equity and also make use of resources to grant facility, granted by the government. Although the WACC for companies without debt is higher, the companies surveyed prefer to adopt a structure without third-party resources, such as banks and funds, for strategic reasons directly linked to agency theory. Also, evidence of an opportunistic approach and the pecking order theory in determining the structure was found. As a research limitation points up the difficulty of accessing the information on the balance sheets and income statements of the sample companies.